ISO 9000:2000 in focus [ - Murray, Ferguson; Nicholas and Smith (Australia : Nicholas and Smith, 2000)
This video programme features two international case studies. They are NCR Financial Solutions Group Ltd (UK) and TRW Aeronautical Systems Australia Ltd. Each case study company describes examples of their continuous improvement achievements and activities. The programme connects these activities with the structure and intent of ISO 9001:2000, focusing on the key enhancements within the standard. The video also covers the applicatiopn of the process approach and continual improvement in a quality management system
Directed and edited, Murray Ferguson ; writer and producer Nicholas and Smith
DVD Drive
Keywords: Iso 9000 series standards -- Case studies; Quality assurance -- Standards; Quality control -- Standards -- Handbooks, manuals, etc